PREVALENCE OF PROTEUS SPP AND ITS ANTIBIOTIC RESISTANCE PATTERN IN UTI PATIENTS AT DISTRICT MARDAN, KHYBER PAKHTUNKHWA - Junaid, Muhammad; Haq, Naeem Ul; Ali, Hamad; Ullah, Zahid; Ahmad, Saghir; Khan, Imad; Niaz, Falak (International Journal of Pharma and Bio Sciences, 2025)
Introduction: Urinary tract infections (UTIs) are a significant global health concern, with Proteus spp emerging as a key pathogen known for its resistance to antibiotics and association with complications like kidney stones. Despite its clinical importance, data on the prevalence and resistance patterns of Proteus spp in District Mardan, Pakistan, remain scarce. This study aimed to determine the prevalence of Proteus spp in UTIs and analyze its antibiotic resistance profile to inform better treatment strategies. Methodology: A cross-sectional study was conducted from June 2024 to May 2025 at Mardan Medical Complex Hospital, involving 684 UTI patients. Urine samples were collected and processed using standard microbiological techniques, including culture on MacConkey and CLED agar, Gram staining, and biochemical tests. Antibiotic susceptibility was assessed via the Kirby-Bauer disk diffusion method against 19 antibiotics, with resistance interpreted per CLSI guidelines. Statistical analysis was performed using SPSS version 23.0. Results: Out of 684 samples, 48% (n=329) showed bacterial growth, with Proteus spp accounting for 17% (n=119) of isolates, making it the second most prevalent pathogen after Escherichia coli (22%). The highest resistance was observed against Co-Amoxiclav (93.3%), and Ciprofloxacin (83.2%), while Meropenem (100%) and Fosfomycin (93.3%) were the most effective. Resistance patterns varied significantly by age and gender, with higher resistance noted in middle-aged adults (36–59 years) and males. Conclusion: The study highlights alarming resistance rates among Proteus spp isolates in District Mardan, particularly to first-line antibiotics. These findings underscore the need for antimicrobial stewardship programs and region-specific treatment guidelines to combat the growing threat of multidrug-resistant UTIs. Further research is recommended to explore genetic mechanisms of resistance and evaluate alternative therapies.